Intermittent Fasting Inhibits High-Fat Diet–Induced Atherosclerosis by Ameliorating Hypercholesterolemia and Reducing Monocyte Chemoattraction - Chen, Yuanli; Su, Jiamin; Yan, Yali; Zhao, Qian; Ma, Jialing; Zhu, Mengmeng; He, Xiaoyu; Zhang, Baotong; Xu, Hongmei; Yang, Xiaoxiao; Duan, Yajun; Han, Jihong (Frontiers in Pharmacology, 2021)
Atherosclerosis is a major pathology for cardiovascular diseases (CVDs). Clinically, the intermittent fasting (IF) has been observed to reduce the risk of CVDs. However, the effect of IF on the development of atherosclerosis has not been fully elucidated. Herein, we determined the protection of IF against high-fat diet–induced atherosclerosis in pro-atherogenic low-density lipoprotein receptor deficient (LDLR-/-) mice and the potentially involved mechanisms. The LDLR-/- mice were scheduled intermittent fasting cycles of 3-day HFD feeding ad libitum and 1 day fasting, while the mice in the control group were continuously fed HFD. The treatment was lasted for 7 weeks (∼12 cycles) or 14 weeks (∼24 cycles). Associated with the reduced total HFD intake, IF substantially reduced lesions in the en face aorta and aortic root sinus. It also increased plaque stability by increasing the smooth muscle cell (SMC)/collagen content and fibrotic cap thickness while reducing macrophage accumulation and necrotic core areas. Mechanistically, IF reduced serum total and LDL cholesterol levels by inhibiting cholesterol synthesis in the liver. Meanwhile, HFD-induced hepatic lipid accumulation was attenuated by IF. Interestingly, circulating Ly6Chigh monocytes but not T cells and serum c-c motif chemokine ligand 2 levels were significantly reduced by IF. Functionally, adhesion of monocytes to the aortic endothelium was decreased by IF via inhibiting VCAM-1 and ICAM-1 expression. Taken together, our study indicates that IF reduces atherosclerosis in LDLR-/- mice by reducing monocyte chemoattraction/adhesion and ameliorating hypercholesterolemia and suggests its potential application for atherosclerosis treatment.